Sistem Pengambilan Keputusan Menentukan Media Pembelajaran Daring Efektif Bagi Siswa SMP Al Qolam Kotaagung Menggunakan Metode Weight Product - Renaldo, Riki; Arida, Syiar Irmania; Nurheti, Nurheti (Institut Bakti Nusantara, 2024)
This study aims to develop a decision-making system in determining effective online learning media for students of SMP Al Qolam Kotaagung using the Weight Product (WP) method. In today's digital era, choosing the right learning media is very important to improve the quality of online learning, especially at the junior high school level. The Weight Product method was chosen because of its ability to optimize the assessment of various media alternatives based on predetermined criteria, such as ease of access, interactivity, availability of materials, and suitability to the curriculum. This study uses a quantitative approach with data analysis techniques that involve giving weights to each relevant criterion. SMP Al Qolam Kotaagung is under the auspices of the Ministry of Education and Culture, Tanggamus Regency Education Office. The online school application is an important application for all students during this pandemic. Many students use the WhatsApp, Classroom, Zoom, Edmodo, Google Meet applications. In other cases, many students use these applications. Therefore, this analysis determines which media is effective, in analyzing the application using the Weighted Product method. The results of the study are expected to provide recommendations for appropriate and effective learning media, so that they can increase the effectiveness of the online learning process at SMP Al Qolam Kotaagung. In addition, this system can be a reference for other schools in choosing the right online learning media according to the needs and characteristics of students.